2013
DOI: 10.2527/jas.2012-5692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased milking frequency during early lactation on milk yield and udder health of primiparous Holstein heifers1

Abstract: In dairy cows, increased milking frequency (IMF) during early lactation stimulates an increase in milk yield that partially persists through the remainder of lactation. However, the effects of IMF on lactation performance and udder health of primiparous heifers have not been clearly established. The objective of this study was to determine the effects of IMF during early lactation on milk yield and composition, udder edema, and teat-end condition of primiparous Holstein heifers. Thirteen heifers were assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
3
21
1
1
Order By: Relevance
“…Cependant, le rendement matières grasses du lait et en matières protéiques du lait augmente en raison de l'augmentation de la production de lait. Les mêmes résultats ont été observés par Soberon et al (2011), Wright et al (2013) et Hardin (2015 qui ont trouvé une augmentation significative du rendement en matières grasses du lait et en matières protéiques du lait.…”
Section: Mesures De La Production Et Prélèvements Des éChantillons Deunclassified
“…Cependant, le rendement matières grasses du lait et en matières protéiques du lait augmente en raison de l'augmentation de la production de lait. Les mêmes résultats ont été observés par Soberon et al (2011), Wright et al (2013) et Hardin (2015 qui ont trouvé une augmentation significative du rendement en matières grasses du lait et en matières protéiques du lait.…”
Section: Mesures De La Production Et Prélèvements Des éChantillons Deunclassified
“…At this point, as has been evaluated for cows (Erdman and Varner, 1994;De Koning et al, 2002;Wagner-Storch and Palmer, 2003;Wade et al, 2004;Albeni et al, 2005;Speroni et al, 2006;Gygax et al, 2007;Stelwagen et al, 2013;Wright et al, 2013) we want to test the possible correlation between milking frequency of AMS (independent variable) and daily milk yield of AMS (dependent variable) to state if there is an increase in milk yield due to increase of milking frequency. Since the two variables are quantitative and they follow a normal distribution, for this reason, the Pearson product-moment correlation coefficient (r) can be used as measure of correlation, as shown by Hauke and Kossowski (2011).…”
Section: Data Selection and Analysismentioning
confidence: 99%
“…It was previously reported that milk yield and flow rate, are dependent on the milking interval (Hogeveen et al, 2001). For cows, an increase in milk yields from 6 to 25% in complete lactations, has been observed when milking frequency is increased from two to three times per day (Amos et al, 1985;Stelwagen et al, 2013;Wright et al, 2013). Various authors observed that in cows milked more than twice per day in AMS, there was a production increase of 12% compared to cows milked twice per day in the conventional system (De Koning et al, 2002;Wagner-Storch and Palmer, 2003;Wade et al, 2004); other researches did not noticed a relationship between the increase of daily milking frequency in AMS and the daily milk yield (Erdman and Varner, 1994;Albeni et al, 2005;Speroni et al, 2006;Gygax et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…AMS reduces heavy-workload and allows milking frequency monitoring of each individual cow, based on its production level or lactation stage, without any additional labour costs [12]. Everything else remains unchanged, the cows milked more frequently during lactation, normally produce more milk than the cows milked twice a day [13]. Even if many factors can affect the behavior of dairy cows on a farm, the cows milked by AMS can carry out their daily activities with more freedom and have more interaction opportunities with their environment [14].…”
Section: Introductionmentioning
confidence: 99%